Response of workers of Atta sexdens rubropilosa (Hymenoptera: Formicidae) to mandibular gland compounds of virgin males and females - Bento, J. Maurício S.; Nascimento, Ruth R. do; Bergmann, Jan; Della Lucia, Terezinha M. C.; Morgan, E. David (Physiological Entomology, 2007)
The secretion from the mandibular glands of males of the leaf‐cutting ant Atta sexdens rubropilosa is responsible for the reaction of workers outside the nest at the time of sexual swarming. Workers respond with excitability and aggression when presented with the natural mixture of 4‐methyl 3‐heptanol and 4‐methyl‐3‐heptanone, which is contained in the secretion of the male mandibular glands. Workers respond quickly to fractional amounts of one male equivalent. 4‐Methyl‐3‐heptanone, from the virgin female mandibular glands causes much less response in workers, whereas an equimolar mixture of male and female pheromones gives a still less clear response. The male pheromone plays the most important part in the communication of workers outside the nest at this time.
Keywords: Aggression; Excitation; Leaf-cutting ants; 4-methyl-3-heptanol; 4-methyl- 3-heptanone; Pheromone; Virgin males; Virgin females; Worker behaviour